Student Reasoning Based on Mathematical Ability in Solving HOTS Problems through Differentiated Learning - Dian Septi Nur Afifah; Nur Ika Fatmawati (Athena: Journal of Social, Culture and Society, 2024)
The mathematical abilities of students with reasoning are closely interrelated. The HOTS-type problem is an effort to improve reasoning ability. The ability of students to solve HOTS questions is still relatively low. Through a differentiated learning model, it is expected to help students in the learning process that suits their needs. The purpose of this study is to describe the application of differentiated learning models and describe the mathematical reasoning ability of students who have low, medium, and high abilities. This type of research is qualitatively descriptive with instruments in the form of observation sheets, questionnaires, test questions and interviews. Data analysis techniques include data reduction, data presentation, and conclusions. Test the validity of data using triangulation techniques. The results of this study show that differentiated learning can improve students' ability to reason. Four indicators of mathematical reasoning are, students' ability to present mathematical problems in the form of written statements, students' ability to make conjectures, students' ability to manipulate mathematics, and students' ability to draw conclusions from problems. Subjects with a high level of reasoning meet two indicators. Whereas subjects with moderate levels of reasoning met only three indicators and subjects with low levels of reasoning met only two indicators. Mathematics teachers should provide learning that is in accordance with the learning style of students and students should also do HOTS type questions more often.